Changing the Size and Surface Roughness of Polymer Nanospheres Formed Using a Microfluidic Technique - Kucuk, Israfil; Edirisinghe, Mohan (Springer, 2015)
Solid polymer nanospheres with contrasting size and surface roughness were prepared using a V-shaped microfluidic junction device. Polymethysilsesquioxane (PMSQ) polymer dissolved separately in either methanol, or ethanol, or propanol or butanol was used, and the nanospheres produced were collected in distilled water at two different temperatures (23A degrees C and 100A degrees C). Each polymer solution together with a volatile liquid, perfluorohexane, was fed into the inlet channels of the microfluidic device. The process of nanosphere generation was recorded by high-speed camera imaging. Only PMSQ solutions of ethanol and propanol generated well-defined nanospheres. The influence of the solvents and the nanosphere collection temperature on nanosphere size distribution and surface roughness was assessed using scanning electron microscopy, which showed that solvent selection was crucial in tailoring the size distribution of the nanospheres and that the nanospheres collected at 100A degrees C had a noticeably rougher surface. The temperature also helped to vary the size distribution of the nanospheres. Nanospheres containing Evans blue dye were also prepared, and those with a rough surface exhibited a very different dye release profile compared with those having a smooth surface. In fact, the release profile changes due to a size differential can be largely compensated for by having a rough surface.
Keywords: Composite-Particles; Drug-Delivery; Silica Nanospheres; Nanoparticles; Itraconazole; Dissolution; Shape